Outcome of pregnancy following IVF/IUI complicated by ovarian torsion: case reports - Sachdeva, Garima; Gainder, Shalini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ovarian torsion though uncommon after in vitro fertilization (IVF)/ intrauterine insemination (IUI), but if not diagnosed early can lead to ischemic necrosis of the ovary. The reported incidence of ovarian torsion after IVF/IUI is 0.025-0.2% and is primarily attributed to controlled ovarian stimulation (COS). Here we present three case reports of ovarian torsion after IVF/IUI reported in a government hospital, India. The first case was referred to our institute after IVF with acute onset abdominal pain. Diagnosis of ovarian torsion was made. In this patient, ovaries could be salvaged by early diagnosis and intervention and she even delivered a 2.95 kg girl baby in the same pregnancy. The second case also followed IVF done in our institute and by early diagnosis and intervention, we could salvage the ovary. The third case followed IUI, but due to delayed presentation, the patient had to undergo ipsilateral salpingo-oopherectomy. A total of 1562 IUI and 98 IVF were done at our institute last year, of which only one case each of IUI and IVF landed up in ovarian torsion. The significance of this article is to discuss the diagnosis and management of ovarian torsion and to reiterate the importance of early diagnosis and management.